Neriidae (Diptera: Schizophora) from Mexico: new species, new records and an identification key - Gomes, Lucas R. P.; Sepúlveda, Tatiana A.; Pedraza-Lara, Carlos (Zootaxa, 2023)
We conducted a study of material from the Colección de Artrópodos de Referencia Forense, UNAM (CARF), Colección Nacional de Insectos, UNAM (CNIN) and Colección de Insectos del Bosque Seco, Estación de Biología Chamela, UNAM (EBCH), which revealed three new distributional records of cactus flies species in Mexico as follows: Cerantichir enderleini (Hennig, 1937), Eoneria blanchardi Aczél, 1951, and Glyphidops durus (Cresson, 1926). This study also described two new species: Cerantichir mexicana Gomes & Sepúlveda and Eoneria ramirezi Gomes & Sepúlveda. We update the distribution records of the cactus flies (Neriidae) distributed in Mexico. The list of species includes: Glyphidops filosus (Fabricius, 1805), Glyphidops flavifrons (Bigot, 1886), Glyphidops filosus (Fabricius, 1805), Glyphidops xanthopus (Schiner, 1868), Nerius pilifer Fabricius, 1805, Nerius plurivittatus Bigot, 1886, Nerius purpusianus Enderlein, 1922, Odontoloxozus longicornis (Coquillett, 1904), and Odontoloxozus pachycericola Mangan & Baldwin, 1986. This study increases the number of species known to occur in Mexico from eight to 13.